(untitled) (Journal of Laboratory Animal Science, 2024)
Atherosclerosis is one of the important life style diseases of human beings. There are several animal models in vogue for studying the patho-physiology of Atherosclerosis. It is usually done by inducing pressure overload of aorta. In this study we attempted two different murine models by constriction of thoracic aorta (ascending aorta) and by constriction of abdominal aorta, using metal clips. It was observed that thoracic aorta banding requires expertise, expensive equipment and an increased mortality rate compared to abdominal aorta banding. But the time period for the development of cardiac hypertrophy was lesser in thoracic method (2-4 months) compared to abdominal aorta approach (20-24 months).